2015
DOI: 10.5301/jva.5000393
|View full text |Cite
|
Sign up to set email alerts
|

Proper Tip Position of Central Venous Catheter in Pediatric Patients

Abstract: The carina is a good landmark for the upper border of the cavoatrial junction. Length of carina to cavoaterial juction was associated with age. The rates of malposition and re-intervention and the patient's exposure to radiation can be reduced by using ultrasound during the catheter insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Therefore, the carina is not a good landmark for newborns and infants; it has been shown that the catheter tip should be localized at least 0.5 cm for smaller infants (body length: 47e57 cm) and 1 cm for older infants (body length: 58e108 cm) above the carina to ensure that it is outside the pericardial sac [58] (LoE 3). Similarly, it has been shown that the mean distance from the carina to the atriocaval junction was 22.0 ± 9.98 mm [59]. In children beyond infancy the carina can be used as a landmark.…”
Section: Positioning Of the Catheter Tipmentioning
confidence: 90%
“…Therefore, the carina is not a good landmark for newborns and infants; it has been shown that the catheter tip should be localized at least 0.5 cm for smaller infants (body length: 47e57 cm) and 1 cm for older infants (body length: 58e108 cm) above the carina to ensure that it is outside the pericardial sac [58] (LoE 3). Similarly, it has been shown that the mean distance from the carina to the atriocaval junction was 22.0 ± 9.98 mm [59]. In children beyond infancy the carina can be used as a landmark.…”
Section: Positioning Of the Catheter Tipmentioning
confidence: 90%
“…The carina in children has been examined in many studies using computed tomography (Ahn and Chung, ), trans‐esophageal echocardiography (Yoon et al, ), and cadavers (Schuster et al, ; Albrecht et al, ; Inagawa et al, ). As in adult studies, pediatric cross‐sectional imaging‐based assessments showed carina–SVC/RA junction distances as great as 3 cm (Yoon et al, ; Ahn and Chung, ). The authors argue that this is still helpful, as in all cases the carina is superior to the SVC/RA junction, therefore it facilitates placement of a CVC in the SVC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no specific relationship of the CVC depth of the EL and RL to patients' age was illustrated. Although the length and the position of the SVC‐RAJ were associated with age, our EL and RL were comparable to the TEE in all age‐groups. The measurement of specific patient anatomical distance as surrogated to their SVC‐RAJ distance regardless of their age may explain the satisfactory results.…”
Section: Discussionmentioning
confidence: 53%
“…The difference might be due to differences in the study population. In addition, our predetermined optimal target zone was narrower because the SVC length in children was shorter than in adults (4.5 vs 7.1 cm) …”
Section: Discussionmentioning
confidence: 99%